Simulation Effect Of Hot Gas Impingement On Nacelle Lip Skin - Syed, Mohammad Harith Yaccob (Universiti Sains Malaysia, 2017)
Ice accumulation during flight includes the accumulation of icing on the nacelle lip skin of the aircrafts engines. The accumulation on the ice on the inner surface of the lipskin can be hazardous to any flying aircraft [2]. Computational Fluid Dynamics (CFD) has been widely used to study the effect of ice accretion onto the nacelle lip skin. This study however utilizes the fluid structure interaction (FSI) to study the effect of hot gas impingement on the nacelle lip skin towards the thermal properties of the material. It was found that the material used for this study, AL 1 series, 2 series and 7 series has a temperature dependent behavior which is closely related to their microscopic properties. This study has shown that the tensile strength of the materials decreases as the temperature increases and this study also has concluded that aluminum 7 series is the most suitable material to be used for the nacelle lip skin material